Effect of covid-19 vaccination on long covid: systematic review. Issue 1 (28th February 2023) - Byambasuren, Oyungerel; Stehlik, Paulina; Clark, Justin; Alcorn, Kylie; Glasziou, Paul
Abstract : Objective: To determine the effect of covid-19 vaccination, given before and after acute infection with the SARS-CoV-2 virus, or after a diagnosis of long covid, on the rates and symptoms of long covid. Design: Systematic review. Data sources: PubMed, Embase, and Cochrane covid-19 trials, and Europe PubMed Central (Europe PMC) for preprints, from 1 January 2020 to 3 August 2022. Eligibility criteria for selecting studies: Trials, cohort studies, and case-control studies reporting on patients with long covid and symptoms of long covid, with vaccination before and after infection with the SARS-CoV-2 virus, or after a diagnosis of long covid. Risk of bias was assessed with the ROBINS-I tool. Results: 1645 articles were screened but no randomised controlled trials were found. 16 observational studies from five countries (USA, UK, France, Italy, and the Netherlands) were identified that reported on 614 392 patients. The most common symptoms of long covid that were studied were fatigue, cough, loss of sense of smell, shortness of breath, loss of taste, headache, muscle ache, difficulty sleeping, difficulty concentrating, worry or anxiety, and memory loss or confusion. 12 studies reported data on vaccination before infection with the SARS-CoV-2 virus, and 10 showed a significant reduction in the incidence of long covid: the odds ratio of developing long covid with one dose of vaccine ranged from 0.22 to 1.03; with two doses, odds ratios were 0.25-1; with three doses, 0.16; and with any dose, 0.48-1.01. Five studies reported on vaccination after infection, with odds ratios of 0.38-0.91. The high heterogeneity between studies precluded any meaningful meta-analysis. The studies failed to adjust for potential confounders, such as other protective behaviours and missing data, thus increasing the risk of bias and decreasing the certainty of evidence to low. Conclusions: Current studies suggest that covid-19 vaccines might have protective and therapeutic effects on long covid. More robust comparative observational studies and trials are needed, however, to clearly determine the effectiveness of vaccines in preventing and treating long covid. Protocol registration: Open Science Framework https://osf.io/e8jdy .